Mental imagery of speech and movement implicates the dynamics of internal forward models - Tian, Xing; Poeppel, David (Frontiers in Psychology, 2010)
The classical concept of efference copies in the context of internal forward models has stimulated productive research in cognitive science and neuroscience. There are compelling reasons to argue for such a mechanism, but finding direct evidence in the human brain remains difficult. Here we investigate the dynamics of internal forward models from an unconventional angle: mental imagery, assessed while recording high temporal resolution neuronal activity using magnetoencephalography (MEG). We compare two overt and covert tasks; our covert, mental imagery tasks are unconfounded by overt input/output demands – but in turn necessitate the development of appropriate multi-dimensional topographic analyses. Finger tapping (studies 1-2) and speech experiments (studies 3-5) provide temporally constrained results that implicate the estimation of an efference copy. We suggest that one internal forward model over parietal cortex subserves the kinesthetic feeling in motor imagery. Secondly, observed auditory neural activity 170 ms after motor estimation in speech experiments (studies 3-5) demonstrates the anticipated auditory consequences of planned motor commands in a second internal forward model in imagery of speech production. Our results provide neurophysiological evidence from the human brain in favor of internal forward models deploying efference copies in somatosensory and auditory cortex, in finger tapping and speech production tasks, respectively, and also suggest the dynamics and sequential updating structure of internal forward models.